A new method for water clarification using filtration - Радовенчик, Вячеслав Михайлович; Костриця, Анастасія Олегівна; Радовенчик, Ярослав Вячеславович; Сіренко, Людмила Вікторівна (Eastern-European Journal of Enterprise Technologies, 2013)
The paper gives the results of studying the effectiveness of a new method of phase separation using materials with capillary properties. It was found that processing of bentonite suspension by its conventional passing through a paper filter is accompanied by a low average filtering velocity and short operation time caused by intensive calmatation of pores by highly disperse particles. As a result, despite the relatively high efficiency of phase separation (residual content of bentonite particles in the filtrate - about 0.3 mg/dm3), the overall efficiency of separation is quite low because of the need for periodic restoration of filtering capacity of porous medium. A new method of phase separation, using materials with capillary properties, allows creating simple, cheap and effective devices for separating liquid and solid phases. Determining factors of separation process and their influence on the intensity of fluid motion in the porous medium were defined, comparative assessment of effectiveness of the proposed method with conventional filtration was conducted, basic parameters of separation with bentonite suspension processing were determined. It was also found that using the new method, the average velocity of fluid motion is twice higher than that of similar methods for conventional filtration.